2010
DOI: 10.4103/0974-8237.77670
|View full text |Cite
|
Sign up to set email alerts
|

Malignant cord compression: A critical appraisal of prognostic factors predicting functional outcome after surgical treatment

Abstract: Objectives:Advanced tumor disease and metastatic spinal cord compression (MSCC) are two entities with a high impact on patients’ quality of life. However, prognostic factors on the outcome after primary decompressive surgery are less well-defined and not yet standardized. The aim of this review was to identify prognostic variables that predict functional or ambulatory outcomes in surgically treated patients with symptomatic MSCC.Materials and Methods:We conducted MEDLINE database searches using relevant keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Nonetheless, it seems somewhat intuitive that patients with preserved ambulatory capacity would be able to mobilize to a greater extent following surgery and protect themselves from the development of complications that may contribute to early death, such as pneumonia or pulmonary embolism. 1,14 Our results regarding the influence of primary tumor type on 90-day survival are not surprising. Patients in this analysis with metastatic lung cancer demonstrated a 64% reduction in the odds of survival at 90 days, synonymous with a number of efforts that have shown poor prognosis for patients with this type of cancer.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Nonetheless, it seems somewhat intuitive that patients with preserved ambulatory capacity would be able to mobilize to a greater extent following surgery and protect themselves from the development of complications that may contribute to early death, such as pneumonia or pulmonary embolism. 1,14 Our results regarding the influence of primary tumor type on 90-day survival are not surprising. Patients in this analysis with metastatic lung cancer demonstrated a 64% reduction in the odds of survival at 90 days, synonymous with a number of efforts that have shown poor prognosis for patients with this type of cancer.…”
Section: Discussionmentioning
confidence: 54%
“…[1][2][3][4][5][6][7][8][9][10]13,14,15,19,20 Several studies have indicated that surgery is more advantageous than nonoperative measures in terms of functional outcome, pain control, and preservation of ambulatory capacity. 1,2,8,9 Invariably, not all patients with spinal metastases can benefit from a surgical procedure, especially as such interventions may be physiologically taxing to oncology patients and are known to carry moderately high rates of postoperative morbidity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, the recommendation for early surgical decompression (<48 h) was supported by two studies [13,25] with a similar distribution of patients regaining ambulation (8-9%). In an inhomogeneous collective of MSCC patients, a mean of 62.1% (range 23-95%) of patients maintained ambulation after surgical treatment [26]. In our study, one third of the patients (35%) representing the most frequent tumors causing MSCC remained ambulatory and half of our patients (51%) were able to ambulate postoperatively.…”
Section: Discussionmentioning
confidence: 67%
“…Surgery offers the best potential to maintain ambulation status for patients who were ambulatory before the resection of tumor [22] . It also yields improved Frankel grade classification, a common measure of the completeness of a spinal cord injury, by at least one level postoperatively and decreased pain symptoms [23] .…”
Section: Prevalence and Pathology Of Spinal Cord Tumorsmentioning
confidence: 99%